Follicular thyroid cancer in developing countries: a 10-year study)a retrospective study. ( - علوش علي محمد (Latakia University Journal -Medical Sciences Series, 2022)
Background: The most common endocrine tumor is thyroid cancer. Follicular thyroid carcinoma (FTC) accounts for 5-10%of all thyroid cancers. Patients with FTC frequently present with more advanced diseases and a highe roccurrence of distant metastases because of the propensity of vascular invasion. FTC is mainly treated with surgery while radioactive iodine (RAI) therapy is the main adjuvant therapy according to the American Thyroid Association guidelines. Methodology: This was a retrospective observational study of FTC patients aged 18 and above conducted at Al-Assad University Hospital, and Tishreen University Hospital, Lattakia, Syria from 1 January 2010 to 31 December 2019. Results: A total of 404 patients with thyroid carcinoma were sorted, of which 40 (10.1%) were FTC cases. Overall, 50%of the patients were in the age group of 41-60 years, and the female-to-male ratio was 1.5:1. The majority of patients (60%) presented with neck swelling, followed by bone and lung metastasis in 20% and compressive symptoms in another 20%. On fine needle aspiration cytology (FNAC), 50% had Bethesda category III-IV nodules while 10% had Bethesda category II. Overall, 50% had a total thyroidectomy while 50% had a lobectomy followed by a completion thyroidectomy. On histopathology, 23 (57.5%) patients had minimally invasive FTC while 17 (42.5%) had widely invasive FTC. A total of 17 (42.5%) patients had received RAI 30- 100 mCi while 10 (25%) received more than 100 mCi.- Conclusions: FTC can present with both local or metastatic symptoms. The atypical presentation of metastatic FTC should be considered, diagnosed, and managed early to limit mortality and morbidity. Ultrasound is the best diagnostic investigation of choice followed by FNAC. Surgery is the mainstay of treatment and should be followed by RAI in select cases. Thus, understanding the trend of FTC and proper planning and utilization of the resources will help developing countries in effectively treating the FTC.